The 96-week outcomes and pharmacokinetics of long-acting cabotegravir plus rilpivirine in South Africans - Rosie Mngqibisa; Yashna Singh; Catherine Orrell; Johan Lombaard; Sandy Griffith; Conn Harrington; Ronald D’Amico; William Spreen; Marty St Clair; Christine Latham; Louise Garside; Rodica Van Solingen-Ristea; et al. (Southern African Journal of HIV Medicine)
Background: Evaluating long-term efficacy, safety and pharmacokinetics of long-acting cabotegravir + rilpivirine (CAB+RPV LA) in sub-Saharan African populations is important because of the region’s unique demographics and antiretroviral therapy resistance patterns.